Analysis of Blood flow Through Artery with Mild Stenosis - Pokhrel, Puskar R.; Kafle, Jeevan; Kattel, Parameshwari; Gaire, Hari Prasad (Journal of Institute of Science and Technology, 2020)
Arterial stenosis is an abnormal condition in arteries due to the deposition of fats and other substances, called atherosclerosis. As it restricts the blood flow, it may induce a heart attack. Employing the Navier-Stokes equations, we consider the blood flow in an artery with the presence of a stenosis in an axisymmetric shape. We analyze the blood flow dynamics in cylindrical form by evaluating pressure, pressure drop against the wall, shear stress on the wall. We also analyze the dynamics by evaluating the ratio of pressure drop with stenosis to the pressure drop without stenosis against the wall, and the ratio of maximum to minimum shear stresses with the ratios of various thicknesses of stenosis to radius of the artery.